Update on Primary Biliary Cirrhosis - Jenny Heathcote (Canadian Journal of Gastroenterology)
The diagnosis of primary biliary cirrhosis (PBC) is most often made in the asymptomatic phase, sometimes before the development of abnormal liver biochemistry. The antimitochondrial antibody remains the predominant hallmark, although not all patients test positive, even when the most sensitive techniques are used. The etiology of PBC remains elusive; studies suggest that the interlobular bile duct destruction is immune based, and associated autoimmune diseases are common. There are no surrogate markers that predict outcome in asymptomatic patients, whose chance of survival is less than that of age- and sex-matched populations but much better than the median survival of eight years in patients with symptomatic PBC. Symptoms common in this disease are fatigue, pruritus and xanthelasma, as well as complications of portal hypertension and osteoporosis. Treatment includes symptomatic and preventive measures, as well as specific therapeutic measures. Immunosuppressive therapy has yielded disappointing results in the long term management of PBC, and the only therapy shown to improve survival is the hydrophobic dihydroxy bile acid ursodeoxycholic acid. Treatment at a dose of 13 to 15 mg/kg/day is optimal, given in separate doses or as a single dose at least 4 h from giving the oral anion exchange resin cholestyramine, which may be used to control pruritus. However, liver transplantation remains the only cure for this disease, and the best postoperative survival is seen in patients whose serum bilirubin does not exceed 180 µmol/L at the time of liver transplantation. Recurrence takes place but is rarely symptomatic and does not deter from the benefits of transplantation.